A Comparative Study of Passenger Multitasking Activities on Commuting and Leisure Electrified Intercity Railways - Xing Yao; Chunhui Jing; Yaoxuan Huang; Jinyi Zhi (Journal of Advanced Transportation)
The electrification of intercity railways plays a significant role in energy conservation and emission reduction. Research on passenger travel activities to optimize vehicle services can help to understand how best to improve passenger attraction and the use of intercity railways. In this study, we conducted observational research on two electrified intercity railways that were segregated by the attributes, leisure, and commute. The purpose was to determine the influence of line attribute, passenger gender, age, and seat availability on the types of activities performed onboard, with specific attention placed on the use of information and communication technology (ICT). Using structured observations, the travel multitasking activity data of 467 passengers were collected on two intercity railways in real-life situations. Using the chi-square test and binary logistic regression analysis, it was found that line attribute, gender, age, and seat availability have an impact on passenger activities. Differences in factors affecting passenger activities were also found according to the nature of their travel, whether for commute or leisure. Our results suggest that passengers on the leisure line prefer to engage in some social activities. For example, the probability of conversation among passengers on the leisure line was 3.47 times that of the commuting line, and the middle-aged and elderly travelers on this line were more likely to be in a daze and look around. The probability of taking a break for passengers on the commuting line was 3.625 times that of the leisure line, and passengers who were not seated on this line were found to be more likely to be idle. In addition, male travelers and young travelers preferred to engage in ICT immersive activities, such as using mobile phones, while women, middle-aged, and elderly travelers were more likely to engage in non-ICT immersive activities. Seated passengers were more likely to engage in simultaneous multitasking activities, rest, and conversations than passengers without seats.